The The Effect of Flexitarian Diet on Waist Circumference and Sagittal Abdominal Diameter (SAD) in Obese Female Students: Pengaruh Diet Flexitarian terhadap Lingkar Pinggang dan Diameter Sagital Abdominal pada Mahasiswi Obesitas - Akifah, Adzro'ul; Dieny, Fillah Fithra; Nuryanto, Nuryanto; Noer, Etika Ratna; Tsani, A. Fahmy Arif (Amerta Nutrition, 2023)
Background: Central obesity causes various diseases. Abdominal fat is associated with metabolic disturbances. Dietary interventions targeting abdominal fat are reported to have health benefits. A plant-based diet is known to be beneficial in reducing abdominal fat. Objectives: This study aims to see the effect of a flexitarian diet on abdominal fat through waist circumference and SAD. Methods: This research used a quasi-experimental design with a pre-post-test control group design. The research sample size was 21 obese female students aged 19-25 in Semarang. Subjects were selected using the consecutive sampling method and divided into treatment groups (11 subjects) and control groups (10 subjects). The four-week flexitarian diet treatment group included three main meals and two snacks, while the control group was not given any dietary intervention. However, both groups (all subjects) were given nutrition and obesity education through lectures and leaflets. Anthropometric data on body weight, waist circumference, and SAD were taken before and after the intervention. Statistical analysis was performed using paired t-test, independent T-test, Mann Whitney, and ANCOVA. Results: Intakes between groups during the intervention showed statistical energy, fat, and fibre differences. SAD between the treatment group (-1.2±0.6cm) and the control group (0.2±1.5cm) showed a significant difference (p=0.010). There was no significant difference in waist circumference between the groups, but the decrease in the treatment group was more significant (-6.6±5.5cm). Physical activity did not affect changes in SAD (p=0.210), while diet treatment affected changes in SAD (p=0.010). Conclusions: Changes in SAD showed a significant difference between groups after intervention. Changes in waist circumference were insignificant between groups, but the decrease was more significant in the treatment group.